Exchange Rates in the Periphery and International Adjustment Under the Gold Standard - Catao, Luis (IMF Working Papers; Working Paper ;, 2003)
The role of exchange rate flexibility in the periphery of the gold standard has been grossly overlooked. This paper builds a new dataset on trade-weighed exchange rates for the period 1870-1913 and finds that large currency movements in periphery countries operating inconvertible paper-money and silver-standard regimes induced major fluctuations in effective exchange rates worldwide. We relate the phenomenon to the international trade structure at the time and show that such currency fluctuations had powerful effects on trade flows. We conclude that nominal exchange rate flexibility in the periphery was an important ingredient of international payments adjustment under the gold standard.